026 Universidade Catholica de Mozambique (UCM), Beira: the second medical school in Mozambique. Issue 3 (9th February 2012) - Evans, M; Lunn, M P; Steidel, K; Stam, J; Day, J L; Manji, H
Abstract : The past 20 years has seen a boom in medical education in Sub-Saharan Africa with more than 60 medical schools opening during this period (2). In '06, Africa had 18 doctors per 100 000 population, compared to 360 per 100 000 in the UK (3). The picture for Neurology is even more dismal-while Western Europe has ∼one neurologist/20 000 population, Africa has an average of one/three million (4). Mozambique, in southeast Africa is bordered by the Indian Ocean to the east. It shares a border with six countries. Tb prevalence is 323 per 100 000 population. HIV prevalence 11.5%-this continues to rise and is ∼30% in Beira (3). The Medical School at UCM opened in 2001. The first doctor graduated in 2007. The University has now trained 102 doctors. None of the medical graduates have emigrated–yet! A major issue of concern now is the lack of post graduate teaching. The Neurology curriculum, is taught by three international lecturers who visit during a 4 week 'block' dedicated each year to Neurology. There are no Neurologists in Beira. We discuss our experiences gleaned from visiting this Medical school and attached University hospital over the past 8 years. We present several instructive cases that illustrate the burden of Neurological disease in Mozambique; look at the management of challenges and obstacles the university faces such as retaining faculty staff and medical graduates, provision of adequate resources, curriculum innovations, international collaborations and maintenance of an appropriate standard of education.